Size-selected Au nanoparticles on FTO substrate: Controlled synthesis by the Rayleigh-Taylor instability and optical properties. (December 2016) - Ruffino, F.; Gentile, A.; Zimbone, M.; Piccitto, G.; Reitano, R.; Grimaldi, M.G.
Abstract: In this work we study the plasmonic properties of Au nanoparticles on fluorine doped-tin-oxide (FTO) correlating these properties to the structural characteristics of the nanoparticles. We use the laser annealing approach to dewet thin Au films deposited on the FTO surface so to form the Au nanoparticles. However, we found, in view of the optimization of the optical properties, that better structural characteristic for the nanoparticles (i. e, larger mean radii and lower size dispersion) are obtained by irradiating the Au films maintaining the sample immersed in glycerol solution instead of the standard set-up with the samples in air. In fact, when thin films are rapidly melted inside a bulk fluid, the ensuing gas pressure gradients can produce huge acceleration forces that can destabilize the film leading to the Rayleigh-Taylor instability as the leading nanostructuring process. The same experiments performed with the samples in air lead to a subpopulation of very small nanoparticles (diameter lower than 20 nm) which contributes drastically to the parasitic optical absorption of the nanoparticles. The structural characteristics of the nanoparticles and the corresponding optical properties are investigated changing the thickness of the starting deposited Au film. Simulations of the optical behavior of the FTO/Au nanoparticles system, based on finite element analysis, are, also, reported to better interpret the experimental results. The overall fabrication procedure is, so, optimized in view of the improvement of the plasmonic optical properties of the FTO/Au nanoparticles system for future solar cells applications. Graphical abstract: Highlights: Au nanoparticles (NPs) are produced on FTO surface by laser annealing of deposited films. Laser annealing are performed with the samples in air or immersed in glycerol. The Rayleigh-Taylor (RT) instability is the main structuration process for the NPs in glycerol. The NPs produced by the RT instability in glycerol are larger and monomodal in size. The NPs produced by the RT instability in glycerol present better plasmonic properties.